E-GOVERNANCE’S ROLE IN GENDER EQUALITY AND SUSTAINABLE DEVELOPMENT - Sharma, Alka; Sanjay (ShodhKosh: Journal of Visual and Performing Arts, 2025)
E-governance is the integrated use of communication and information technology to deliver government information and services to a country’s citizens. E-learning initiatives within e-governance, such as Google Meet, Zoom, YouTube, e-Pathshala, e-Library, e-PG Pathshala, etc., have greatly benefited women in the field of education. Through various digital platforms, women are pursuing their studies and achieving success in various fields. Various digital government schemes have had a positive impact on women. The government’s e-governance schemes have made most tasks paperless. The goal of e-governance is to empower citizens through access and use of information. People, processes, technology, and resources are the key pillars of e-governance. The e-governance scheme aims to provide citizens with access to all government services through Common Service Centers. For centuries, women have been denied the right to equal participation in the nation’s social and economic activities. The concept of gender equality has become a common concern, especially in India. Due to the patriarchal nature of society, women are unable to receive the respectful benefits of various government initiatives, even though India promises digital inclusion and digital opportunities. Rural India still suffers from the digital divide. Unleashing the full potential of e-governance initiatives without access to ICT is impossible. Gender differences impact connectivity and access opportunities. E-governance is not a panacea, yet it offers men and women an opportunity to overcome the social evils of gender inequality. The United Nations is holding a virtual meeting to promote sustainable development. The Declaration of the United Nations Conference on Environment and Development recognizes the right of every country to pursue social and economic progress and places on states the responsibility to adopt models of sustainable development.